Growth factors mediated differentiation of mesenchymal stem cells to cardiac polymicrotissue using hanging drop and bioreactor. (7th January 2015) - Konstantinou, Dimitrios; Lei, Ming; Xia, Zhidao; Kanamarlapudi, Venkateswarlu
Abstract: Heart disease is the major leading cause of death worldwide and the use of stem cells promises new ways for its treatment. The relatively easy and quick acquisition of human umbilical cord matrix mesenchymal stem cells (HUMSCs) and their properties make them useful for the treatment of cardiac diseases. Therefore, the main aim of this investigation was to create cardiac polymicrotissue from HUMSCs using a combination of growth factors [sphingosine‐1‐phosphate (S1P) and suramin] and techniques (hanging drop and bioreactor). Using designated culture conditions of the growth factors (100 nM S1P and 500 µM suramin), cardiomyocyte differentiation medium (CDM), hanging drop, bioreactor and differentiation for 7 days, a potential specific cardiac polymicrotissue was derived from HUMSCs. The effectiveness of growth factors alone or in combination in differentiation of HUMSCs to cardiac polymicrotissue was analysed by assessing the presence of cardiac markers by immunocytochemistry. This analysis demonstrated the importance of those growth factors for the differentiation. This study for the first time demonstrated the formation of a cardiac polymicrotissue under specific culture conditions. The polymicrotissue thus obtained may be used in future as a 'patch' to cover the injured cardiac region and would thereby be useful for the treatment of heart diseases.